Pengaruh Ukuran Perusahaan, Kinerja Keuangan, dan Kepemilikan Institusional Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (Studi Kasus pada Perusahaan Indeks LQ-45 yang Terdaftar di Bursa Efek Indonesia pada Periode 2019 – 2021) - Lia Mardiya Ninsih; Maslichah Maslichah; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aimed to investigate the impact of institutional ownership, firm size, and financial success on disclosure of social responsibility. Using a quantitative methodology, this investigation. The LQ-45 Index businesses listed on the Indonesia Stock Exchange for the 2019–2021 period were the focus of this research, which was carried out at www.idx.go.id. The investigation will start in September 2022 and continue until it is finished. The LQ-45 index businesses listed on the Indonesia Stock Exchange from 2019 to 2021 make up the study's population. To collect 21 samples, sampling was done using a purposive sampling technique and preset criteria. According to the study's findings, institutional ownership, financial performance, and company size all have a substantial impact.Keywords: Company size, financial performance, institutional ownership and disclosure of corporate social responsibility